An Analysis on Various Perspectives on Internet Marketing Communication: Understanding the Impact of Internet Marketing Communication (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The study mainly covers the acquisition process of Internet marketing after touching upon the basic knowledge of Internet marketing, how the Internet adapts to the marketing mix, as well as companies’ and consumers’ perspectives in pursuing Internet marketing. The research builds upon the literature in electronic commerce and past research in marketing with the objective of understanding factors that impact a product’s adaptability to online marketing. A review of marketing channel choice literature reveals a set of factors and channel choice functions that are considered important in making channel decisions. Using this as a basis, four major channel functions, namely, product customization, availability, logistics, and transaction complexity are considered relevant in understanding the implications for Internet marketing. The social networking that allows the quick and easy dissemination of information and mis-information is in part a product of changes in online communication channels, but these communication channels are in part enabled by such social networking. From a marketing perspective, we are at a pioneering stage in understanding how these work. This article suggests an infrastructure that could be useful in studying how online communication channels are emerging and how they might evolve in the future.